PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI HW HOTEL PADANG - Supa, Rahmi Dera (journal of residu, 2019)
This study aims to determine the effect of work motivation on employee work productivity at HW Hotel Padang. The type of research conducted in this study is a quantitative descriptive research using causative associative methods. The population in this study were all employees at HW Hotel Padang. The sampling technique in this study was a saturated sample with a sample of 45 employees. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. Technical analysis uses the help of the SPSS Computer Program version 16.00. The results of the study show: 1) The work motivation in HW Padang Hotel is at an average score of 56% with a fairly good category, 2) The work productivity of employees at HW Hotel Padang is at an average score of 89% with very good categories, 3) Results Person Product Moment correlation shows that there is a positive and significant influence between work motivation and work productivity of employees at HW Padang Hotel, with the results of linear regression testing obtained F value of 10.435 with significant 0.002 <0.05, which means variables X and Y are significant. Then the work motivation variable influences employee work productivity variables, so Ha is accepted and Ho is rejected.The value of R square in this study amounted to 0.195 this means that the variable Employee Motivation has an effect of 19.5% on Employee Productivity at HW Hotel Padang and 80.5% is influenced by other variables